International Day for Disaster Risk Reduction 2022 - International Water Management Institute (International Water Management Institute, 2022)
Climate change is making extreme weather events more severe and frequent, disproportionately effecting middle- and low-income countries. IWMI works with partners to develop science-based solutions to help communities to prepare for, mitigate, and respond to disasters.